DNA methylation-based diagnosis confirmation in a pediatric patient with low-grade glioma: a case report - Morgacheva, Daria; Ryzhova, Marina; Zheludkova, Olga; Belogurova, Margarita; Dinikina, Yulia (Frontiers in Pediatrics, 2023)
Pediatric CNS tumors comprise highly heterogenic and complicated group of diseases. Historically, diagnosis confirmation of these tumors was routinely based on histological examination, however, recently obtained data demonstrate that such diagnostic approach is not completely accurate and could lead to misdiagnosis.Recently, quantity and quality of molecular diagnostic methods have greatly improved, that had influenced current classification and treatment approach to pediatric CNS tumors. Nowadays molecular methods, including DNA methylation profiling, are imprescriptible part of diagnostics of pediatric brain and spinal tumors.In this paper we present a case of an infant with posterior fossa tumor, that demonstrated non-specific morphology and whose diagnose has been verified only after DNA methylation.